PENGARUH PERCEIVED JUSTICE TERHADAP WORD OF MOUTH, TRUST DAN REVISIT INTENTION YANG DIMEDIASI OLEH RECOVERY SATISFACTION - Sembodo Herry C (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2008)
The purpose: of this study is to assess the relative influences of distributive (DJ), procedural (PJ), and interactional (Li) justice on customer satisfaction on service recovery and to examine the relationship between recovery satisfaction and subsequent customer relationships: trust, word-of-riwuth (WOM), and revisit intention.Methodology: On-site surveys were administered to collect data from insurance customer who bought, and experienced a service failure.Findings: The effect of DJ on satisfaction with service recovery was stronger than those of PJ and IL Since DJ, PJ, and II have significant effects on trust, WOM, and revisit intention through recovery satisfaction, recovery satisfaction was found to be an important mediating variable. In addition, the mediational role of trust between recovery satisfaction and WOM/revisit intention is substantial. Thus, in a case where strong trust is formed between the service provider and the customer, a long-term relationship can be expectedKeyword : Service failure, Service recovery, Complaint handling, Perceived justice, Trust, Revisit Intention, Word of Mouth